Parkinson's disease patients show reduced cortical‐subcortical sensorimotor connectivity. Issue 4 (9th November 2012) - Sharman, Michael; Valabregue, Romain; Perlbarg, Vincent; Marrakchi‐Kacem, Linda; Vidailhet, Marie; Benali, Habib; Brice, Alexis; Lehéricy, Stephane
<x xml:space="preserve">Abstract</x> Reduced dopamine input to cortical and subcortical brain structures, particularly those in the sensorimotor network, is a hallmark of Parkinson's disease (PD). The extent to which dopamine dysfunction affects connectivity within this and other brain networks remains to be investigated. The purpose of this study was to measure anatomical and functional connectivity in groups of PD patients and controls to determine whether connectivity deficits within the cortico–basal ganglia thalamocortical system could be attributed to PD, particularly in sensorimotor connections. A neuroimaging paradigm involving diffusion‐weighted magnetic resonance imaging (MRI) and resting‐state functional MRI was implemented in a large cohort of PD patients and control subjects. Probabilistic tractography and functional correlation analyses were performed to map connections between brain structures and to derive indices of connectivity that were then used to compare groups. Anatomical connectivity deficits were demonstrated in PD patients, specifically for sensorimotor connections. Functional deficits were also found in some of the same connections. In addition, functional connectivity was found to increase in associative and limbic connections in PD patients compared with controls. This study lends support to findings regarding the dysfunction of the sensorimotor circuit in PD. As deficits in anatomical and functional connectivity within this circuit were in some cases concordant in PD patients, a possible link between brain structure and function is suggested. Increases in functional connectivity in other cortico–basal ganglia thalamocortical circuits may be indicative of compensatory effects in response to system deficits elsewhere. © 2012 Movement Disorder Society